Investigating Undergraduate Students Discourse Markers Used in Final Project Article of English Department at Universitas Negeri Semarang - Wening Nur Habibah Alif; Dwi Rukmini; Sri Wuli Fitriati (English Education Journal, 2023)
Students' writing quality in academic writing must still be investigated. Especially in terms of coherence and arrangement between sentences, sometimes inaccuracies cause sentences written to be less meaningful. This study aims to: 1) describe the use of discourse markers in the final undergraduate student article projects, especially in the discussion section, and 2) explain how far the quality of undergraduate students' writing is in applying discourse markers. Discourse Markers are conjunctions used as hooks between sentences so that the linkages between sentences are maintained, and the meaning of the sentences can be easily understood. This study applies the theory of Discourse Markers by Fraser (2009), which is complemented by an explanation of material on Academic Writing based on the book Writing Academic English by Oshima and Hogue (2006). The instrument is in the form of documentation. This study's qualitative data for analysis came from 11 undergraduate students' final project articles focused on the discussion part only. Furthermore, the data is categorized into three types of Discourse Markers: contrastive, elaborative, and inferential. After that, the analysis results are also provided in the form of the quality of student writing which has been categorized as appropriate and less appropriate.